2018
DOI: 10.37751/parameter.v3i1.57
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Sinergi Oposisi Biner Formulasi Dengan Tujuan Dasar Laporan Keuangan Akuntansi Syari’ah

Abstract: Tujuan dalam penelitian ini pada dasarnya untuk memberikan kontribusi bagi akuntansisyari’ah pada level teori, khususnya memformulasikan tujuan dasar (basic objectives)dari laporan keuangan (financial statement) akuntansi syari’ah. Alat analisis yangdigunakan dalam makalah ini adalah sinergi oposisi biner yang diilhami oleh nilai-nilaidari tradisi Islam dan Tao. Alat analisis ini pada dasarnya meng- gabungkan dua halyang berbeda (dan bahkan bertolak belakang) menjadi satu kesatuan yang tidakterpisahkan, misaln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, referring to the Islamic Accounting Theory described by Baydoun and Willett (1994), it can be concluded that economic growth based on sharia principles must be able to produce social justice, wealth distribution, and strengthen equality in society (Hartati, 2018). So that in this study, the selection of variables is based on two main aspects, namely the concept of social justice and wealth distribution in line with the Maqashid Syariah Index (X1), and the distribution of power in line with the value of Islamic business good governance (X2).…”
Section: Shariah Business Good Governancementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, referring to the Islamic Accounting Theory described by Baydoun and Willett (1994), it can be concluded that economic growth based on sharia principles must be able to produce social justice, wealth distribution, and strengthen equality in society (Hartati, 2018). So that in this study, the selection of variables is based on two main aspects, namely the concept of social justice and wealth distribution in line with the Maqashid Syariah Index (X1), and the distribution of power in line with the value of Islamic business good governance (X2).…”
Section: Shariah Business Good Governancementioning
confidence: 99%
“…Sharia Accounting Theory in Hartati (2018), which is viewed from the perspective of Baydoun and Willett (1994), stated that economic growth must create social justice, wealth distribution, and more equitable power. Therefore, financial statements based on Islamic Sharia cover various aspects, such as financial, social, environmental, material, mental, and spiritual.…”
Section: Introductionmentioning
confidence: 99%